Transmission Control Protocol Performance Comparison Using Piggyback Scheme In WLANS - Ahmad Milad, Ali; Muhamad Noh, Zul Azri; Shibghatullah, Abdul Samad; Sahib, Shahrin; Ahmad, Rabiah; Algaet, Mustafa Almahdi (Science Publications, 2013)
The main problem at wireless networks is the overhead at MAC layer; when the data physical rate is increasing it causes increasing the overhead and decreasing at the MAC efficiency. In this study we study the performance comparison of TCP protocol in WLANs with and without using piggyback. The study of results concerning of implemented both mechanisms in NS2 simulator and find out the good performance from this comparison. Based on the results from our experiments show that the Piggyback scheme is one of the efficient ways to reduce the overhead at MAC wireless networks.